Resíduo da indústria siderúrgica: remoção eficaz de fosfato de águas e evidências de um potencial fertilizante - Silva, Juliana Monteiro da (2022)
This work offers an alternative to mitigate the problem of eutrophication of water bodies, which can result in a serious threat to the environment and aquatic life, and the possible shortage of food production when using steel waste in adsorption/desorption systems of phosphate. Produced on a scale of thousands of tons per year, these residues can contribute to air, soil and water pollution when disposed of without proper management. In this context, the potential of phosphate remediation by adsorption was evaluated, using waste from the steel industry with subsequent release of the nutrient for fertilization purposes, thus addressing three important environmental problems. Kanbara reactor dust (KR) and blast furnace sludge (BFS) were applied to elucidate the phosphate removal mechanism, employing the sequential extraction method, kinetic and thermodynamic studies. The morphological and chemical characterizations carried out demonstrate the residues have an irregular morphology, with most of the pores in the mesopores range and consisting mainly of alkaline metals and metallic oxides. Efficient 99% phosphate removal was observed for both residues in 24 h, and speciation studies indicated that KR interacts very strongly with phosphate, making its reuse less viable. For the BFS, the thermodynamic data indicated a physisorption process offering the advantage of phosphate desorption, which in this case was about 97% applying a basic eluent, demonstrating the potential release of the nutrient to the soil. With no need for a regeneration solution, the adsorbent was able to adsorb up to 95% phosphate again. The loaded BFS increased the bioavailability of P by 46% compared to the fresh material, demonstrating both the efficiency of phosphate adsorption by the BFS as well as the potential release of bioavailable phosphorus for plants. This set of results demonstrates the applicability of BFS, which dispenses with prior treatment, in the recovery of an essential nutrient, offering the additional advantage of adding value to waste from the steel industry, in line with a sustainable economy.